APLIKASI TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Ulfa Ismayani; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to study the effect and to obtain the best dose of Trichokompos TKKS on the growth of cocoa seeds (Theobroma cacao L.). Research has been conducted at the Experimental Farm of the Faculty of Agriculture, Riau University. This study was conducted from June 2016 to September 2016. This research was experimental research by using Completely Randomized Design (CRD), which consisted of 5 TKKS trichokompos treatments, consisted of: 0 g/5 kg soil (T0), 25 g/5 kg soil (T1), 50 g/5 kg soil (T2), 75 g/5 kg soil (T3) and 100 g/5 kg soil (T4). Each treatment was repeated 4 times , in order to obtain 20 unit experiments which consist of 3 seeds, in which 2 seeds as sample plants and it obtained 60 plant seeds. The observed parameters were a height plant, stem diameter, number of leaves, root shoots ratio and dry weight. Data were analyzed using analysis of variance and the mean of each treatment was tested with Duncan’s New Multiple Range Test at 5 % level. The result of this research showed that the giving of trichokompos TKKS gave significant result towards all of observation parameters. Based on the result, the giving of trichokompos TKSS with dose 75 g/5 kg soil was better to improve the growth of cacao seeds. Keywords : the growth of, cacao seedlings, Trichokompos TKKS.